Photolithographic Microfabrication of Microbatteries for On-Chip Energy Storage - Ma, Yuan; Wang, Sen; Wu, Zhong‑Shuai (Nano-Micro Letters, 2025)
Microbatteries (MBs) are crucial to power miniaturized devices for the Internet of Things. In the evolutionary journey of MBs, fabrication technology emerges as the cornerstone, guiding the intricacies of their configuration designs, ensuring precision, and facilitating scalability for mass production. Photolithography stands out as an ideal technology, leveraging its unparalleled resolution, exceptional design flexibility, and entrenched position within the mature semiconductor industry. However, comprehensive reviews on its application in MB development remain scarce. This review aims to bridge that gap by thoroughly assessing the recent status and promising prospects of photolithographic microfabrication for MBs. Firstly, we delve into the fundamental principles and step-by-step procedures of photolithography, offering a nuanced understanding of its operational mechanisms and the criteria for photoresist selection. Subsequently, we highlighted the specific roles of photolithography in the fabrication of MBs, including its utilization as a template for creating miniaturized micropatterns, a protective layer during the etching process, a mold for soft lithography, a constituent of MB active component, and a sacrificial layer in the construction of micro-Swiss-roll structure. Finally, the review concludes with a summary of the key challenges and future perspectives of MBs fabricated by photolithography, providing comprehensive insights and sparking research inspiration in this field. Highlights: 1 The fundamental principles and step-by-step procedures of photolithography are introduced, and a nuanced understanding of its operational mechanisms and the criteria for photoresist selection is offered. 2 Various specific roles that photolithography plays in microbatteries (MBs) fabrication, including templates for 2D and 3D micropatterns, MB active components, and the sacrificial layer for constructing micro-Swiss-roll structure, are elaborated. 3 The challenges and future directions of MBs fabricated using photolithography, including materials selection, packaging techniques, application, and performance evaluation, are discussed.